An Egg Parasitoid Efficiently Exploits Cues From a Coevolved Host But Not Those From a Novel Host - Bertoldi, Valeria; Rondoni, Gabriele; Brodeur, Jacques; Conti, Eric (Frontiers in Physiology, 2019)
Egg parasitoids have evolved adaptations to exploit host-associated cues, especially oviposition-induced plant volatiles and odours of gravid females, when foraging for hosts. The entire host selection process is critical for successful parasitism and relevant in defining host specificity of parasitoids. We hypothesised that egg parasitoid females are able to exploit cues related to a coevolved host but not those from a novel host. We used the egg parasitoid Trissolcus japonicus, its coevolved host Halyomorpha halys and the non-coevolved host Podisus maculiventris to evaluate this hypothesis. Halyomorpha halys, a polyphagous pest native from eastern Asia, has invaded North America and Europe, resulting in serious damage to crops. Trissolcus japonicus is the most effective egg parasitoid of H. halys in its native area, and thus considered a major candidate for biological control. This parasitoid was detected in North America and Europe as a result of accidental introductions. Laboratory host range of T. japonicus includes P. maculiventris, a Nearctic predatory stink bug used as biological control agent of several pests. We tested in a Y-tube olfactometer the responses of T. japonicus females to tomato plant volatiles induced by oviposition and feeding of either H. halys or P. maculiventris. Additionally, we tested, using long-range and short-range olfactometer set-ups, T. japonicus responses to volatiles emitted by eggs and reproductively mature males and females of H. halys or P. maculiventris. Tomato plants subjected to oviposition and feeding by H. halys were significantly attractive for the wasp in the long-range olfactometer, indicating the activation of an indirect defence mechanism. Furthermore, in the short-range olfactometer, T. japonicus females were attracted by volatile cues from gravid females and mature males of H. halys but not from eggs. By contrast, parasitoid females never responded to volatile cues associated with P. maculiventris, although this non-target host is suitable for complete parasitoid development. Such lack of responses to volatile cues might reduce the probability of T. japonicus locating and parasitizing P. maculiventris under field conditions. Our experimental approach well simulates the parasitoid host-location process and could be combined with the required host specificity tests for risk assessment in biological control programs.